2018
DOI: 10.1016/j.jcis.2017.09.069
|View full text |Cite
|
Sign up to set email alerts
|

Viscoelastic effects on residual oil distribution in flows through pillared microchannels

Abstract: We find that viscoelastic polymers and surfactant solutions can displace more oil compared to Newtonian fluids and nearly inelastic shear thinning polymers at similar Ca numbers. Beyond a critical Ca number, the size of residual oil blobs decreases significantly for viscoelastic fluids. This critical Ca number directly corresponds to flow rates where elastic instabilities occur in single phase flow, suggesting a close link between enhancement of oil recovery and appearance of elastic instabilities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Combining such flow visualization to measurements of the overall pressure drop provides a way to directly link flow structure to macroscopic flow resistance. Such measurements show a dramatic increase in macroscopic flow resistance—mimicking the increase in η app observed in bulk porous media—at the onset of unstable flow (Figure i) . Simulations in model porous geometries can also capture the onset of flow fluctuations and the associated increase in flow resistance .…”
Section: Unstable Flow Of Polymer Solutionsmentioning
confidence: 66%
See 2 more Smart Citations
“…Combining such flow visualization to measurements of the overall pressure drop provides a way to directly link flow structure to macroscopic flow resistance. Such measurements show a dramatic increase in macroscopic flow resistance—mimicking the increase in η app observed in bulk porous media—at the onset of unstable flow (Figure i) . Simulations in model porous geometries can also capture the onset of flow fluctuations and the associated increase in flow resistance .…”
Section: Unstable Flow Of Polymer Solutionsmentioning
confidence: 66%
“…Recent work suggests a key role played by flow instabilities in enhancing fluid recovery. Indeed, microfluidic experiments have shown that unstable flow is often characterized by a dramatic increase in η app , as described in Section —leading to a concomitant increase in Ca . This idea has been directly verified using oil globules trapped in a microfluidic porous medium: injecting polymer solutions can increase the apparent Ca by nearly an order of magnitude, thereby increasing oil recovery ( Figure a,b) .…”
Section: Improved Fluid Recovery From Porous Mediamentioning
confidence: 69%
See 1 more Smart Citation
“…transport of proppant particles used in fracturing fluids and for flow around elements of microporous structures (frequently modelled by microfluidic post arrays) and in which elastic instabilities have been shown to play an important role. [46][47][48][49] However, a drawback of most microfluidic cylinder experiments to date is that, due to typically employed fabrication techniques (such as soft lithography or micromilling), their geometries have been restricted to low aspect ratios (a o 1) and to high blockage ratios (typically b Z 0.5). [50][51][52][53][54][55] The low aspect ratio means the flow field is strongly inhomogeneous along the cylinder axial direction.…”
Section: Introductionmentioning
confidence: 99%
“…Normal stresses due to shear should not be ignored as their contribution may be of the same magnitude as stresses due to extension [19]. De et al [22] numerically and experimentally studied the contribution of shear and extensional flows to the increased normal stresses of viscoelastic polymer solutions in a porous media, while Haward et al [14] investigated this contribution experimentally in a cross-slot device and they both found a large contribution of viscoelastic normal stresses in shear flow at high flow rates where elastic turbulence exists [23,24].…”
Section: Introductionmentioning
confidence: 99%